Lymphatic Valve Dysfunction in Western Diet-Fed Mice: New Insights Into Obesity-Induced Lymphedema - Castorena-Gonzalez, Jorge A. (Frontiers in Pharmacology, 2022)
A two-way connection between obesity and lymphatic dysfunction has now been established. Clinical studies have demonstrated that obesity significantly increases the risk for developing secondary lymphedema. Using animal-models, obesity and metabolic syndrome have been linked to different aspects of lymphatic structural abnormalities and lymphatic dysfunction, including impaired contractility, impaired flow-mediated responses, impaired fluid transport, as well as increased permeability, and abnormal dendritic cell migration among others. Dysfunction of lymphatic valves is a main form of lymphatic dysfunction, known to result in severe edematous phenotypes; however, the extent of lymphatic valve deficiency in secondary lymphedema, including obesity-induced lymphedema, remains unknown. Therefore, the aims of the present study were 1) to determine whether western diet-induced obesity results in lymphatic valve dysfunction, and 2) to determine whether lymphatic valve dysfunction in western diet-induced obesity results from the diet itself, or as a consequence of the metabolic alterations induced by the diet. First, we quantitatively assessed and compared valve function in isolated popliteal and mesenteric collecting lymphatic vessels from control and western diet-induced obese C57BL/6J (WT) mice. Feeding a western diet for 14 weeks induced obesity and elevated plasma glucose and cholesterol levels when compared to controls. The function of lymphatic valves in popliteal lymphatics was not affected by diet-induced obesity; however, significant back-leak of pressure was observed in mesenteric lymphatic valves. Dysfunctional, leaky valves from obese animals also required significantly higher adverse pressure to trigger valve closure. Importantly, when subjected to treatment with a western diet, globally deficient PAI-1 mice were significantly protected against metabolic dysfunction and displayed fully functional, competent mesenteric lymphatic valves. In conclusion, our findings show for the first time that, in association with the metabolic alterations induced by the western diet, lymphatic valve dysfunction can be a critical component of obesity-induced lymphedema.